Medical privacy as an object of civil legal relations - Ayrat R. Davletshin, Kamil M. Arslanov (Opción, 2019)
The present article aims to investigate the place of personal non-property relations in the subject of civil law via general scientific methods such as logical, system-structural, analytical, synthetic and private-scientific methods. As a result, the state of information privacy, as its legal mode, is regarded by the patient as his/her personal non-material (intangible) benefit, satisfying his/her needs. In conclusion, medical privacy is a state of information about the health and private life of a patient in respect of which a certain legal mode is established, which is characterized by the degree of awareness of third parties about this information.